Construction of Novel Bimetallic Oxyphosphide as Advanced Anode for Potassium Ion Hybrid Capacitor. Issue 9 (18th January 2022) - Wang, Shouzhi; Lv, Songyang; Wang, Guodong; Feng, Kun; Xie, Shoutian; Yuan, Guotao; Nie, Kaiqi; Sha, Mo; Sun, Xuhui; Zhang, Lei
Abstract: Potassium ion hybrid capacitors (PIHCs) have attracted considerable interest due to their low cost, competitive power/energy densities, and ultra‐long lifespan. However, the more sluggish insertion kinetics of battery‐type anodes than capacitor‐type cathodes in PIHCs seriously limits their practical application. Therefore, developing advanced anodes with high capacitor and suitable K + intercalation is imperative and significant. A novel core–shell structure of NiCo oxide/NiCo oxyphosphide (NCOP) nanowires are designed and constructed in this study via efficient and facile strategy. Combining the merits of the core–shell structure and the massive active sites in the oxyphosphide layer, the as‐prepared NCOP composites manifest highly reversible capacitors and outstanding rate capability. Meanwhile, the insertion and conversion potassium storage mechanisms of the NCOP are successfully revealed through in situ X‐ray diffraction and density functional theory calculations, respectively. Furthermore, the PIHC was assembled with NCOP anode and borocarbonitride cathode, which displays a large energy density and high‐power density, along with an exceptional capacity retention of ≈90% over 10 000 cycles at 1.0 A g −1 . This work provides the anion regulation strategy for modifying the transition metal oxide and constructing the advancing electrode materials for next‐generation energy storage and beyond. Abstract : Novel bimetallic oxyphosphide nanowires (NCOP) as advanced anode for potassium ion hybrid capacitor are synthesized via a universal anion‐exchange strategy. Benefiting from the massive defects and multiple cation valence of the oxyphosphide and the stable core‐shell structure of the NCOP, the anode exhibits superior potassium storage capability. DFT calculations and In‐situ XRD reveal the potassium storage mechanism of the NCOP.